(untitled) (Leiden, 1998)
The content of indivudual chapters is usually divided into following sections: history of the use of constructed wetlands in a particular country, types of constructed wetlands, main dessign parameters, treatment efficiency,...
Keywords: Constructed wetlands,Sewage,Xây dựng đất mềm; Purification,Biological treatment; Europe